Abdominal cocoon- A rare of sub acute intestinal obstruction- a case report. - Gatea, Hasan K.; Gatea, Hasan K.; Al gailani, Faik T. (Journal of the Faculty of Medicine Baghdad, 2011)
Abstract this is a case report of abdominal cocoon also referred to as sclerosing encapsulating peritonities in 32 year-old female patient who presented to us with history of recorrent abdominal pain ,